ALFALFA Nutrient and irrigation management. Issue 3 (24th August 2016) - Undersander, Dan; Renz, Mark; Sheaffer, Craig; Shewmaker, Glen; Sulc, Mark
Abstract : Once a good stand of alfalfa has been established, continued production and stand life depends on good management practices, which include maintaining soil nutrients, applying manure judiciously, and irrigating properly. The following article is a section from the revised (2015) Alfalfa Management Guide, which is available for purchase here: www.societystore.org . Earn 1 CEU in Nutrient Management by reading this article and completing the quiz at www.certifiedcropadviser.org/certifications/self‐study/771 .